(untitled) (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2026)
This study analyzes the figure of Maryam in the Qur’an as a representation of women’s piety and autonomy through the perspective of embolic anthropology and gender status. This stadi has the purpose of examining Maryam’s piety not only as a symbol of sexual purity, but as a symbol of spiritual independence that plays an active role with piety in the midst of patriarchal social status. The method used is qualitative using textual and interpretative analysis limited by QS. Ali-Imron [3]: 42-47 and QS. Maryam [19]: 16-23, making Tafsir Al-Qurthubi’ as the primary reference. The data analysis used the symbolic anthropological theories of Clifford Geertz and Sherry B. Ortner to examine those related to religious symbols, women’s bodies, and patriarchal cultural constructions. This research reveals how classical interpretations tend to highlight Maryam’s piety through the concept of ’iffah (chastity) and moral control over women’s bodies is something that reflects patriarchal norms. However, the Qur’anic narrative also presents Maryam as a religious sub-jel who is independent, dialogue, and establishes a direct relationship with Allah without a male intermediary. In conclusion, Maryam not only presents moral purity and nobility, but also becomes a symbol of women’s spiritual power and autonomy which opens up a wider and contextual space for gender representation in the Qur’an.